Social Control through Public Disclosure on Tax: A New Approach to Enhance Tax Compliance - Neni Susilawati; Vallencia Vallencia (Indonesian Association for Public Administration (IAPA), 2021)
The government always strives to boost tax revenue with various instruments and approaches, but the results are often not as expected. Of the various strategies, the tax payer- behavior approach is still rarely applied. The re-emergence of the issue of tax data publication through Pandora Paper after previously being surprised with the Panama Paper, is the right momentum to look back at tax transparency with the naming and shaming instrument. But before that, research is needed on whether the application of this approach is suitable to be applied in Indonesian society with a heterogeneous socio-cultural character. Therefore, the purpose of this study is to explore the level of social control of the community as an initial capital in implementing the public disclosure on tax in an effort to increase tax compliance. Quantitative approach was conducted with online survey as data collection technique. As the result, Indonesian people have strong social control, especially with the existence of social media. The majority of respondents support if the publication of tax data is applied. Public disclosure on tax has a significant role in shaping tax morals.